2020
DOI: 10.1038/s41598-020-78354-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoxia on the double-strand break repair after photon and carbon ion irradiation of radioresistant HNSCC cells

Abstract: DNA double-strand breaks (DSBs) induced by photon irradiation are the most deleterious damage for cancer cells and their efficient repair may contribute to radioresistance, particularly in hypoxic conditions. Carbon ions (C-ions) act independently of the oxygen concentration and trigger complex- and clustered-DSBs difficult to repair. Understanding the interrelation between hypoxia, radiation-type, and DNA-repair is therefore essential for overcoming radioresistance. The DSBs signaling and the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 60 publications
3
27
1
Order By: Relevance
“…Representative images of foci per nucleus are shown in Figure S8 for each cell line in the basal condition, at 2 h and 24 h. Following hypoxia, the kinetics of RAD51 foci were enhanced after photon exposure in all the subpopulations studied. By contrast, no modification occurred after C-ion exposure, a result in accordance with our previous studies [38]. Interestingly, silencing HIF-1α after hypoxia induced a strong decrease of RAD51 in response to both radiations in non-CSCs and CSCs, as shown in Figure 6b.…”
Section: Silencing Hif-1α Decreases Hr In Response To Photon and C-iosupporting
confidence: 91%
See 3 more Smart Citations
“…Representative images of foci per nucleus are shown in Figure S8 for each cell line in the basal condition, at 2 h and 24 h. Following hypoxia, the kinetics of RAD51 foci were enhanced after photon exposure in all the subpopulations studied. By contrast, no modification occurred after C-ion exposure, a result in accordance with our previous studies [38]. Interestingly, silencing HIF-1α after hypoxia induced a strong decrease of RAD51 in response to both radiations in non-CSCs and CSCs, as shown in Figure 6b.…”
Section: Silencing Hif-1α Decreases Hr In Response To Photon and C-iosupporting
confidence: 91%
“…Cells were irradiated at a dose rate of approximately 2 Gy/min with 250 kV photons (X-RAD320, Lyon-Sud Medical School, Lyon, France) and C-ions at the initial energy of 290 MeV/n, center of 6 cm Spread-Out Bragg Peak (SOBP) with the Heavy-Ions Medical Accelerator of Chiba, at National Institute of Radiological Sciences (Chiba, Japan) [16,20,37]. Time points were performed from 30 min after irradiation (time needed to eliminate neutrons in the irradiation room and come back to the bench) to 24 h. The radiobiological parameters (α, β, RBE at 10% survival) calculated according to the linear-quadratic model were previously published for the four subpopulations studied [16,38]. Following a comparative study for DNA Damage Repair kinetics between X-rays and C-ions, and since RBEs were dependent on both the populations tested and the oxygen concentration, all experiments were performed at an equivalent physical dose of 2 Gy photons [38].…”
Section: Irradiationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiotherapy is widely applied in HNSCC, either alone or in multimodal therapy strategies comprising surgery, radiotherapy and chemotherapy. Despite the many technical innovations in recent years, there remains a significant rate of radioresistance in patients [ 35 , 36 ], highlighting an urgent medical need for new concepts in radiotherapy practice. In this regard, it has been suggested that the succinate pathway is related to patient outcome or response to cancer therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%